Comparative Study of the effects of Tricogramma pretiosum (Hym., trichogrammatidae) releases and Triflumuron Applications on Epinotia aporema (Lep., Tortricidae) in Birdsfoot Trefoil Seedbeds - Baáo, C.=700 1 Grille, G.; Alzugaray, R.; Pintureau, B.
(En, Es)
Ilus., 16 ref.
Keywords: TORTRICIDAE; CONTROL BIOLOGICO; REGULACION DEL CRECIMIENTO; LEGUMINOSAS; ESPAÑA